Surface crack modelling in an engine compressor disc. (October 2019) - Giannella, V.; Citarella, R.; Perrella, M.; Shlyannikov, V.
Highlights: A full FEM and a FEM-DBEM approach to simulate fatigue crack-growth are presented. A high pressure compressor disc of a turbofan engine is used as study case. A sound agreement between numerical results is obtained. A numerical-experimental comparison is provided showing a good agreement. Abstract: This work presents two distinct procedures to perform fatigue crack-growth simulations in a high pressure compressor disc of a turbofan engine. Two distinct load cases were separately considered as applied to the compressor disc under analysis: one load case was used to replicate a full-size experimental fatigue bench test, whereas the other was used to simulate the real in service operating conditions of the engine. Two distinct approaches were adopted for the simulations: a full FEM approach and a particular variant of a FEM-DBEM submodelling strategy. It is worth mentioning that, with the latter approach, the only needed boundary conditions for the DBEM submodel analysis are tractions applied on the crack faces; such tractions are derived by the global FEM analysis. A sound agreement between numerical and experimental outcomes was obtained.